EVALUASI PEMANFAATAN MEDIA E-LEARNING DENGAN MENGGUNAKAN MODEL ASSURE PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SMK 17 AGUSTUS 1945 SURABAYA - Khoirun Nisa (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2021)
This study aims to determine the effectiveness of the benefits of e-learning media using the ASSURE model in Islamic Religious Education learning at SMK 17 Agustus 1945 Surabaya. This research is a descriptive quantitative research. The sample in this study was class X majoring in RPL SMK 17 Agustus 1945 Surabaya totaling 20 students. The data collected in this study were through questionnaires and interviews and then analyzed descriptively. Respondents of this study were teachers and students of SMK 17 Agustus 1945 Surabaya who were directly involved with e-learning. The results of this study indicate that the implementation of e-learning learning at SMK 17 August 1945 Surabaya is in accordance with the quality standards of the implementation of e-learning in the planning and design components of making learning materials with a tendency of 34.60% for the delivery of e- learning components with a tendency of 34.7%. %, and in the learning component with the ASSURE model, with a tendency of 44.3% and it is known that the minimum and maximum scores of the two variables of the use of e-learning media are 31 and 46 respectively. While the minimum and maximum scores of learning using the model ASSURE are 13 and 24 respectively. With this it can be concluded that the evaluation of the use of e-learning media with the ASSURE model is good and effective in applying to learning by paying attention to the procedures for implementing e-learning in schools.